Shared Sensorialities: Reshaping Cinema through Neurodiversity. A Conversation with Steven Eastwood on The Stimming Pool (2024) - Eastwood, Steven; Michaud, Maxime; Dorval, Justine (Cinémas, 2025)
In this conversation, filmmaker and researcher Steven Eastwood reflects on the collaborative process behind the creation of The Stimming Pool (2024), co-directed with neurodivergent members of the Neurocultures Collective. He discusses the ethical and aesthetic stakes of a co-creation in which atypical subjectivities are not merely represented but actively participate in redefining the very codes of cinema. Reflecting on working methods grounded in slowness, trust, and attentiveness, Eastwood describes the development of an “autistic camera” and the exploration of non-linear narrative forms grounded in alternative perceptual regimes. Far from an illustrative or explanatory approach, the film embraces sensory and relational co-experimentation. In doing so, it offers a shift in perspective: a cinema shaped through alterity, resonance, and the shared inhabiting of divergent perceptual worlds.